Deinstitutionalisation in Lithuania: Minimal Changes in the “Maximalist” Organisations - Šumskienė, Eglė (Socialinė teorija, empirija, politika ir praktika, 2014)
Summary The article employs the institutional theory to examine the influence of institutional environments on the structure and function of mental health and social care organizations as well as their resistance to the reform. On the basis of statistical data collected by responsible organizations, the dynamics of mental health and social care organizations’ practice, changes in the numbers of clients and employees are analysed. These alterations allow evaluating the status quo and actual direction of the mental health care reform. The usual institutional response to deinstitutionalization is the modification of activities by introducing new services which respond to the emerging requirements. Nevertheless, these are minimal changes since they do not influence the size of an institution and the principles of its work. Innovative attitudes and organisational goals are of declarative character as they do not correspond to the poor institutional reality. Key words: institutional theory, deinstitutionalisation, mental health and social care